2016
DOI: 10.13189/cor.2016.040302
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Gold, Silver and Silver–Gold (Bimetallic) Nanoparticles as Radiosensitizers for Radiation Therapy in Cancer Treatment

Abstract: One of the most recognized and widely used treatment modality in cancer is radiation therapy which depends on the radiosensitivity of tumour tissue. Over the past few years there has been lot of interest in the use of formulations to enhance radiotherapeutic effects, especially using metallic (mainly gold) based nanoparticles. Our goal here is to fabricate nanoparticles (NPs) that can be delivered to tumor tissue to increase its radiosensitivity. This would increase efficiency of radiation absorption by the tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
(19 reference statements)
0
10
0
Order By: Relevance
“…For producing these colloidal AgNPs, the Nd:YAG laser beam with a pulse repetition rate of 10 Hz was bombarded and focused on a high-purity Ag metal plate for 11 h. It can be seen in the figure that the formation of colloidal AgNPs in the three liquid mediums is identified by the color changing of the liquid medium that was previously colorless or clear to golden yellow. The golden yellow color of colloidal silver nanoparticles indicates the formation of silver nanoparticles as reported elsewhere [18].…”
Section: Effect Of Liquid Medium On Silver Nanoparticles (Agnps)mentioning
confidence: 57%
See 1 more Smart Citation
“…For producing these colloidal AgNPs, the Nd:YAG laser beam with a pulse repetition rate of 10 Hz was bombarded and focused on a high-purity Ag metal plate for 11 h. It can be seen in the figure that the formation of colloidal AgNPs in the three liquid mediums is identified by the color changing of the liquid medium that was previously colorless or clear to golden yellow. The golden yellow color of colloidal silver nanoparticles indicates the formation of silver nanoparticles as reported elsewhere [18].…”
Section: Effect Of Liquid Medium On Silver Nanoparticles (Agnps)mentioning
confidence: 57%
“…The distinctive color of AgNPs is the result of the localized surface plasmon resonance (LSPR) phenomenon where silver material absorbs. The LSPR of AgNPs ranges from 380 to 425 nm, which means that they absorb blue or red light, so it will reflect the yellow color [18,[20][21][22]. For further information, it will be discussed in the characterization section.…”
Section: Effect Of Liquid Medium On Silver Nanoparticles (Agnps)mentioning
confidence: 99%
“…Figure 2B is a digital photograph of colloidal BNPs which is brownish-orange in colour. 35 In supporting information, Figure S1, we have shown repeatability of synthesis of BNPs at three different time points using UV-visible spectra. The PEG is a stabilizing Size and Zeta Potential of BNPs with Dynamic Light Scattering Method The stability of the dispersed nanoparticles depends on their pH and the surface charge.…”
Section: Uv-visible Spectroscopy Of Colloidal Bnpsmentioning
confidence: 74%
“…29,30 In recent years, gold-silver nanoalloy or Au-Ag bimetallic nanoparticles gained special attention because of their unique properties such as anticancer agent, radiosensitizers and contrast agent for imaging in comparison with individual monometallic systems. [31][32][33][34][35] To explore the advantageous and synergistic property of an alloy, this is first of such studies, we report here one pot synthesis of colloidal PEGylated bimetallic Au-Ag nanoparticles using PEG 600 by polyol method reducing HAuCl 4 and AgNO 3 simultaneously. These nanoparticles were characterized thoroughly to establish the structure and nano architect and showed anticancer activity, nuclear damage, and potential radiosensitizer against oral cancer cell line.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly, radiosensitizers are classified into five categories: (1) the inhibition of intracellular mercaptan or other endogenous radiation protective substances; (2) radiosensitizer radiolysis to form cytotoxic substances; (3) biomolecular repair inhibitors; (4) thymine analogues that can be incorporated into DNA; (5) oxygen simulants with electrophilic activity [ 10 ]. Many studies have found that nanoparticles synthesized by the atomic number (high-Z) elements have effective lethal effects on tumors [ 11 , 12 , 13 , 14 , 15 ]. When x-rays or γ-rays are applied to metal nanoparticles, a range of effects can occur.…”
Section: Introductionmentioning
confidence: 99%